O modelo de controle estratégico de custos CEC e o ambiente hospitalar filantrópico - Santos, Anderson Fraga dos (Universidade do Vale do Rio do Sinos, 2007)
This dissertation intends to verify the applicability of the referent advanced model of Strategical Control of Costs (SCC) (Diehl, 2004) in the context of a philanthropic university hospital. The first chapter contextualizes the theme and the strategical control of the cost problems in this environment. The second chapter presents the hospital service scene in Brazil focusing upon philanthropic university hospitals. The third chapter shows the theory about strategy and the fourth one includes control and costs. The fifth chapter specifies the SCC Model according to the mentioned environment. The sixth chapter presents the Study of Case methodology applied to PUCRS St. Lucas Hospital. In the seventh chapter the Study of Case sets up the discussion of the model applicability in relation to the new context. At last, the study concludes that the hospital is in an affirmation moment of the leadership strategies in relation to the costs and oranizational configuration as a defender the hospital has reinforced the c
Keywords: estratégias; filantropia; Hospital Universitário; controle de custos; Philanthropic University Hospital; strategy; control of costs; Ciências Sociais Aplicadas